Preparation method of cement mineral-water glass composite grouting material

By using the layered covering structure of graphene oxide and calcium siliconic acid silicon and nanocarbing silicon dioxide in the cement-water glass grouting material, it solves the problem of easy solution caused by uneven diversified water glass, which has significantly improved Mechanical properties and stability of grouting.

CN119349957AActive Publication Date: 2025-01-24ZAOZHUANG MINING GRP ZHONGXING JIANAN ENG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411560052.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The traditional cement-water glass double-liquid grouting material has uneven dispersion of water glass, resulting in excessive local concentration, which in turn causes water glass to be easily dissociated, unstable in performance, and development of deterioration strength, which limits its promotion and application.

Method used

By uniformly dispersed granifying graphene and calcium siliconicate particles, and adding nano-silica to form nano-silicon-oxide graphene-calcium glass silicate coating structure, add saturated sodium hydroxide and// Or in the potassium hydroxide solution, the sodium silicate and/or potassium on the surface of the carrier are generated to avoid water and glass from dissolving.

Benefits of technology

It effectively avoids the dissociation of water glass, improves the mechanical strength and toughness of composite grouting materials, stabilizes performance, delays strength deterioration, and meets complex engineering needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349957A_ABST
    Figure CN119349957A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cement mineral-water glass composite grouting material, which comprises the following steps: (1) dispersing graphene oxide in isopropanol, then adding glassy calcium silicate particles, stirring to uniformly coat the surfaces of the glassy calcium silicate particles with the graphene oxide to obtain a mixed solution; and adding nano silicon dioxide, uniformly mixing, and carrying out solid-liquid separation to obtain a solid product for later use. And (2) adding the solid product into a saturated sodium hydroxide and / or potassium hydroxide solution, then heating and preserving heat, and then carrying out solid-liquid separation to obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate. And (3) uniformly mixing the sodium silicate and / or potassium-graphene oxide-glassy calcium silicate with cement minerals tricalcium silicate, dicalcium silicate and water to obtain the composite grouting material. According to the cement-water glass double-liquid grouting material, the problems that the performance of the grouting material is unstable and the strength is degraded due to the fact that water glass of a traditional cement-water glass double-liquid grouting material is prone to dissociation are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement grouting material preparation, and in particular relates to a method for preparing a cement mineral-water glass composite grouting material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the acceleration of urbanization and the continuous increase in infrastructure construction, the stability, bearing capacity and waterproof performance of soil and rock have become increasingly prominent, and grouting technology has emerged. Grouting technology is not only used in traditional civil engineering fields, but also gradually expanded to underground engineering, mining, environmental governance and other fields, promoting diversified development.

[0004] The main types of grouting used in traditional engineering are polyurethane organic material grouting and cement single-liquid material grouting. The application scope of single-liquid grouting is limited by certain conditions due to factors such as poor stability, uncontrollable gel time, easy stratification and segregation, or environmental pollution. The development of modern materials science, especially the application of new materials such as organic polymers and nanomaterials, has significantly improved the performance of composite grouting materials. Cement-water glass double-liquid grouting technology has the advantages of controllable gel time and high early strength, which can meet the needs of more complex projects and has gradually received widespread attention.

[0005] The combination of cement and water glass can produce higher compressive strength and tensile strength, has good bonding properties, can effectively combine with soil or rock, and improve the reinforcement effect. However, cement-water glass two-liquid grouting material has excessive local concentration due to uneven dispersion of water glass, which in turn causes water glass dissociation, resulting in unstable performance of grouting materials and deteriorated strength development, which also greatly restricts the promotion and application of cement-water glass two-liquid grouting materials. Summary of the invention

[0006] In view of the above problems, the present invention provides a method for preparing a cement mineral-water glass composite grouting material, which effectively solves the problem that traditional water glass is easy to dissociate and has unstable performance. Specifically, the technical solution of the present invention is as follows.

[0007] A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Graphene oxide is dispersed in isopropanol, and then glassy calcium silicate particles are added, and the mixture is continuously stirred so that the graphene oxide is coated on the surface of the glassy calcium silicate particles. After completion, nano-silicon dioxide is added and mixed, and then solid-liquid separation is performed to obtain a solid product for use.

[0008] (2) adding the solid product to a saturated sodium hydroxide and / or potassium hydroxide solution, then heating and heat preservation, and after completion, performing solid-liquid separation to obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate, wherein: the graphene oxide is coated on the surface of the glassy calcium silicate particles, and the sodium and / or potassium silicate is formed by the in-situ reaction of the nano-silicon dioxide adsorbed on the surface of the graphene oxide and the surface of the glassy calcium silicate with the sodium hydroxide and / or potassium hydroxide.

[0009] (3) The sodium silicate and / or potassium-graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water to obtain the cement mineral-water glass composite grouting material.

[0010] Furthermore, in step (1), the graphene oxide is dispersed in isopropanol by ultrasonic dispersion. Optionally, the power of the ultrasonic dispersion is 100-300 W, and the dispersion time is 30-60 min.

[0011] Furthermore, in step (1), the glassy calcium silicate is obtained by mixing calcium carbonate and silicon dioxide in a molar ratio of 0.8 to 1.2:1, sintering, performing solid phase reaction, and then grinding. Optionally, the sintering temperature is 1650 to 1750°C, and the sintering time is 2 to 3 hours.

[0012] Furthermore, in step (1), the particle size of the glassy calcium silicate particles is 20-40 μm.

[0013] Furthermore, in step (1), when the liquid phase system is continuously stirred until it changes from light yellow to colorless and transparent, it indicates that the graphene oxide is coated on the surface of the glassy calcium silicate particles, and then the nano-silicon dioxide is added.

[0014] Furthermore, in step (1), the mass ratio of graphene oxide, glassy calcium silicate and nano-silicon dioxide is 1:1-3:10-25. Optionally, the particle size of the nano-silicon dioxide is 20-50 nm.

[0015] Furthermore, in step (1), the solid-liquid ratio of the graphene oxide, glassy calcium silicate, nano-silicon dioxide and isopropanol is 1 g: 5-10 ml.

[0016] Furthermore, in step (1), the solid-liquid ratio of the solid product to the saturated sodium hydroxide and / or potassium hydroxide solution is 1 g: 5-15 ml.

[0017] Furthermore, in step (2), the heating temperature is 40-60° C., and the heat preservation time is 1-3 hours. Optionally, the heat preservation process is performed by slow stirring at a rate of 30-50 r / min.

[0018] Furthermore, in step (3), the mass ratio of the sodium silicate and / or potassium silicate-graphene oxide-glassy calcium silicate, tricalcium silicate, dicalcium silicate, and water is 1: 0.5~0.8: 0.2~0.5: 0.3~0.5.

[0019] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: First, the present invention uniformly disperses graphene oxide and glassy calcium silicate in an isopropanol solution, and utilizes the large specific surface area of ​​graphene oxide and the rich functional groups and structural defects on the surface to adsorb it on the surface of glassy calcium silicate particles with rough surfaces after grinding, so as to form a glassy calcium silicate structure coated with graphene oxide. After further adding nano-silicon dioxide, it is adsorbed on the defective surface of graphene oxide, and some nano-silicon dioxide particles are adsorbed on the surface of glassy calcium silicate particles, so as to obtain a product of nano-silicon dioxide-graphene oxide-glassy calcium silicate layered coating. The above-mentioned product is added to a saturated sodium hydroxide and / or potassium hydroxide solution (alkali solution), and the silicon dioxide on the surface of the graphene oxide and the surface of the glassy calcium silicate particles reacts with the alkali solution to generate sodium silicate and / or potassium (i.e., water glass) loaded on the surface of the corresponding carrier, and because the graphene oxide is loaded on the surface of the calcium silicate particles at this time, due to the steric hindrance of the particles, the problem of graphene oxide being prone to flocculation and precipitation when encountering alkali solution is avoided. When the sodium silicate and / or potassium-graphene oxide-glassy calcium silicate obtained by the above treatment is combined with cement mineral tricalcium silicate, dicalcium silicate and water to form a grouting material. The tricalcium silicate reacts with water to generate hydrated calcium silicate (CSH) gel and calcium hydroxide, and the sodium silicate and / or potassium further react with the calcium hydroxide to generate hydrated calcium silicate (Ca(OH)2+ Na2O·SiO2 / K2O·SiO2+mH2O→CaO·SiO2·mH2O+2NaOH / KOH), and these hydrated calcium silicates help to further improve the mechanical strength of the composite grouting material. As the above reaction continues, the hydration product calcium hydroxide is continuously consumed and the concentration is continuously reduced, which promotes the continuous hydration of tricalcium silicate, improves its hydration degree, and improves the early mechanical strength of the composite grouting material. In addition, since the water glass component of the present invention is directly or indirectly loaded on the surface of the glassy calcium silicate particles, the problem of excessive local concentration caused by uneven dispersion of water glass, which causes easy dissociation of water glass, leads to unstable performance of the grouting material and causes strength degradation, which is effectively avoided in traditional cement-water glass two-liquid grouting materials.

[0020] Secondly, the NaOH / KOH formed by the above reaction can also excite the surface of the glassy calcium silicate particles, so that the inert glassy silicon-oxygen tetrahedral structure on the surface is depolymerized to form Si(OH)3 - 、SiO2(OH)2 2-The plasma monomer can undergo a secondary reaction with the hydration product calcium hydroxide formed by the dicalcium silicate with a slow hydration start to form a calcium silicate hydrate (CSH) gel, thereby improving the later strength of the grouting material and improving the bonding force between the glassy calcium silicate particles and the grouting material matrix.

[0021] Thirdly, the graphene oxide dispersed in the grouting material can provide nucleation sites for the formation of the above-mentioned CSH gel, thereby promoting hydration and improving the mechanical strength of the grouting material. At the same time, the graphene oxide also has the effect of improving the toughness of the grouting material, hindering the expansion of cracks, and improving the anti-cracking performance of the grouting. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.

[0023] Figure 1 This is a scanning electron microscope image of the cement mineral-water glass composite grouting material prepared in the following Example 1.

[0024] Figure 2 This is a compressive strength test diagram of the specimen prepared in the following Example 1.

[0025] Figure 3 This is a compressive strength test diagram of the test piece prepared in the following Example 4. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.

[0027] Example 1 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Calcium oxide and silicon dioxide are mixed in a molar ratio of 1:1 and stirred evenly, and then heated to 1650°C for sintering for 3 hours. After completion, the mixture is cooled to room temperature, and then the sintered product is ball-milled and sieved to obtain glassy calcium silicate particles with a particle size distribution between 20 and 40 μm for later use.

[0028] (2) Graphene oxide (diameter distribution between 2 and 8 μm, thickness distribution between 1 and 3 nm, oxygen content of 44.7%) was ultrasonically dispersed in isopropanol for 40 min at an ultrasonic power of 200 W. Then, the glassy calcium silicate particles were added, and the mixture was stirred continuously until the liquid phase system changed from light yellow to colorless and transparent, and then nano-silicon dioxide with a particle size of 20 to 50 nm was added. The mass ratio of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide was 1:2:15, and the total mass of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide to the solid-liquid ratio of isopropanol was 1 g:8 ml. After stirring for 10 min, the mixture was filtered for solid-liquid separation, and the obtained solid product was used for standby.

[0029] (3) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g:10 ml, and then heat to 50° C. and keep warm for 2 hours, and stir continuously at a rate of 40 r / min during the warming process. After completion, filter to separate the solid and liquid, and obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate for use.

[0030] (4) The sodium silicate and / or potassium-graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.6:0.35:0.4 and stirred evenly to obtain a composite grouting material.

[0031] Performance test: The composite grouting material prepared in this embodiment is prepared into a test piece (microscopic scanning electron microscope image as shown in FIG. Figure 1 Then, the early and late mechanical strength of the specimens were tested according to the Standard for Test Methods of Physical and Mechanical Properties of Concrete (GBT 50081-2019). The results are shown in Figure 2 And the following table shows: .

[0032] Example 2 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Calcium oxide and silicon dioxide are mixed in a molar ratio of 0.8:1 and stirred evenly, and then heated to 1750°C for sintering for 2 hours. After completion, the mixture is cooled to room temperature, and then the sintered product is ball-milled and sieved to obtain glassy calcium silicate particles with a particle size distribution between 30 and 40 μm for later use.

[0033] (2) Graphene oxide (diameter distribution between 2-8 μm, thickness distribution between 1-3 nm, oxygen content of 44.7%) was ultrasonically dispersed in isopropanol for 60 min at an ultrasonic power of 100 W. Then, the glassy calcium silicate particles were added, and the mixture was stirred continuously until the liquid phase system changed from light yellow to colorless and transparent, and then nano-silicon dioxide with a particle size of 20-50 nm was added. The mass ratio of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide was 1:1:10, and the total mass of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide to the solid-liquid ratio of isopropanol was 1 g:5 ml. After stirring for 10 min, the mixture was filtered for solid-liquid separation, and the obtained solid product was used for standby.

[0034] (3) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g: 5 ml, and then heat to 40° C. and keep warm for 3 hours, and stir continuously at a rate of 50 r / min during the heat preservation process. After completion, filter to separate the solid and liquid, and obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate for use.

[0035] (4) The sodium silicate and / or potassium-graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.5:0.2:0.3 and stirred evenly to obtain a composite grouting material.

[0036] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0037] Example 3 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Calcium oxide and silicon dioxide are mixed in a molar ratio of 1.2:1 and stirred evenly, and then heated to 1680°C for sintering for 3 hours. After completion, the mixture is cooled to room temperature, and then the sintered product is ball-milled and sieved to obtain glassy calcium silicate particles with a particle size distribution between 20 and 40 μm for later use.

[0038] (2) Graphene oxide (diameter distribution between 2 and 8 μm, thickness distribution between 1 and 3 nm, oxygen content of 44.7%) was ultrasonically dispersed in isopropanol for 30 min at an ultrasonic power of 300 W. Then, the glassy calcium silicate particles were added, and the mixture was stirred continuously until the liquid phase system changed from light yellow to colorless and transparent, and then nano-silicon dioxide with a particle size of 20 to 50 nm was added. The mass ratio of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide was 1:3:25, and the solid-liquid ratio of the total mass of the graphene oxide, glassy calcium silicate, and nano-silicon dioxide to isopropanol was 1 g:10 ml. After stirring for 10 min, the mixture was filtered for solid-liquid separation, and the obtained solid product was used for standby.

[0039] (3) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g:15 ml, and then heat to 60° C. and keep warm for 1 hour, and stir continuously at a rate of 30 r / min during the heat preservation process. After completion, filter to separate the solid and liquid, and obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate for use.

[0040] (4) The sodium silicate and / or potassium-graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.8:0.5:0.5 and stirred evenly to obtain a composite grouting material.

[0041] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0042] Example 4 A method for preparing a conventional cement-water glass double liquid grouting material comprises the following steps: (1) Mix 42.5 ordinary Portland cement and water according to the water-cement ratio and stir evenly to form cement slurry (liquid A).

[0043] (2) A water glass solution (modulus 2.3, Baume 30°Bé) is used as liquid B. When used, the liquid A and the liquid B are mixed in a volume ratio of 1:1 to obtain a conventional cement-water glass two-liquid grouting material.

[0044] Performance test: The grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are as follows: Figure 3As shown in the following table, it can be seen that the mechanical strength of the conventional cement-water glass double liquid grouting material of this embodiment is significantly lower than the mechanical strength of the composite grouting material proposed by the present invention in the above-mentioned embodiments 1 to 3: .

[0045] Example 5 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Calcium oxide and silicon dioxide are mixed in a molar ratio of 1:1 and stirred evenly, and then heated to 1650°C for sintering for 3 hours. After completion, the mixture is cooled to room temperature, and then the sintered product is ball-milled and sieved to obtain glassy calcium silicate particles with a particle size distribution between 20 and 40 μm for later use.

[0046] (2) Graphene oxide (diameter distribution between 2 and 8 μm, thickness distribution between 1 and 3 nm, oxygen content of 44.7%) was ultrasonically dispersed in isopropanol for 40 min at an ultrasonic power of 200 W. Then, the glassy calcium silicate particles were added and stirred continuously until the liquid phase system changed from light yellow to colorless and transparent, the mass ratio of the graphene oxide to glassy silicate was 1:2, and the solid-liquid ratio of the total mass of the graphene oxide and glassy calcium silicate to isopropanol was 1 g:8 ml. After stirring for 10 min, the solid-liquid separation was performed by filtering, and the obtained solid product was used for standby.

[0047] (3) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g:10 ml, and then heat to 50° C. and keep warm for 2 hours, and stir continuously at a rate of 40 r / min during the heat preservation process. After completion, filter to separate the solid and liquid, and obtain graphene oxide-glassy calcium silicate for use.

[0048] (4) The graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.6:0.35:0.4 and stirred evenly to obtain a composite grouting material.

[0049] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0050] Example 6 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Add the solid product (prepared in the same manner as in Example 3) to clean water at a ratio of 1 g:15 ml, and then heat to 60°C for 1 hour, stirring continuously at a rate of 30 r / min during the insulation process. After completion, filter to separate the solid and liquid, and obtain graphene oxide-glassy calcium silicate for use.

[0051] (2) The graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.8:0.5:0.5 and stirred evenly to obtain a composite grouting material.

[0052] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0053] Example 7 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Graphene oxide (diameter distribution between 2-8 μm, thickness distribution between 1-3 nm, oxygen content of 44.7%) was ultrasonically dispersed in isopropanol for 60 min at an ultrasonic power of 100 W. Then, ordinary calcium silicate particles (formed by the reaction of sodium silicate solution and calcium chloride) with a particle size distribution between 30-40 μm were added, and the mixture was continuously stirred until the liquid phase system changed from light yellow to colorless and transparent, and then nano-silicon dioxide with a particle size of 20-50 nm was added. The mass ratio of the graphene oxide, calcium silicate and nano-silicon dioxide was 1:1:10, and the solid-liquid ratio of the total mass of the graphene oxide, calcium silicate and nano-silicon dioxide to isopropanol was 1 g:5 ml. After stirring for 10 min, the mixture was filtered for solid-liquid separation, and the obtained solid product was used for standby.

[0054] (2) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g: 5 ml, and then heat to 40° C. and keep warm for 3 hours, and stir continuously at a rate of 50 r / min during the warming process. After completion, filter to separate the solid and liquid, and obtain sodium silicate and / or potassium-graphene oxide-calcium silicate for use.

[0055] (3) The sodium silicate and / or potassium-graphene oxide-calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.5:0.2:0.3 and stirred evenly to obtain a composite grouting material.

[0056] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0057] Example 8 A method for preparing a cement mineral-water glass composite grouting material comprises the following steps: (1) Glassy calcium silicate particles (prepared in the same manner as in Example 3) and nano-silicon dioxide with a particle size of 20 to 50 nm were ultrasonically dispersed in isopropanol for 30 min at an ultrasonic power of 300 W. The mass ratio of the glassy calcium silicate to the nano-silicon dioxide was 3:25, and the solid-liquid ratio of the total mass of the glassy calcium silicate and the nano-silicon dioxide to the isopropanol was 1 g:10 ml. The solid-liquid separation was then performed by filtration, and the obtained solid product was set aside.

[0058] (2) Add the solid product to a saturated sodium hydroxide solution at a ratio of 1 g:15 ml, and then heat to 60°C for 1 hour, stirring continuously at a rate of 30 r / min during the insulation process. After completion, filter to separate the solid and liquid, and obtain a solid product for use.

[0059] (3) The solid product of step (2) is mixed with cement mineral tricalcium silicate, dicalcium silicate and water in a mass ratio of 1:0.8:0.5:0.5 and stirred evenly to obtain a composite grouting material.

[0060] Performance test: The composite grouting material prepared in this embodiment was prepared into a test piece, and then the early and late mechanical strength of the test piece was tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are shown in the following table: .

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a cement mineral-water glass composite grouting material, characterized in that: The steps include: (1) dispersing graphene oxide in isopropanol, then adding glassy calcium silicate particles, stirring continuously to coat the graphene oxide on the surface of the glassy calcium silicate particles, adding nano-silicon dioxide after mixing, and performing solid-liquid separation to obtain a solid product for use; (2) adding the solid product to a saturated sodium hydroxide and / or potassium hydroxide solution, then heating and heat preservation, and after completion, performing solid-liquid separation to obtain sodium silicate and / or potassium-graphene oxide-glassy calcium silicate, wherein: the graphene oxide is coated on the surface of the glassy calcium silicate particles, and the sodium and / or potassium silicate is formed by the in-situ reaction of the nano-silicon dioxide adsorbed on the surface of the graphene oxide and the surface of the glassy calcium silicate with the sodium hydroxide and / or potassium hydroxide; (3) The sodium silicate and / or potassium-graphene oxide-glassy calcium silicate is mixed with cement mineral tricalcium silicate, dicalcium silicate and water to obtain the cement mineral-water glass composite grouting material.

2. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the graphene oxide is dispersed in isopropanol by ultrasonic dispersion; optionally, the power of the ultrasonic dispersion is 100-300 W, and the dispersion time is 30-60 min.

3. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the glassy calcium silicate is obtained by mixing calcium oxide and silicon dioxide in a molar ratio of 0.8 to 1.2:1, sintering, performing solid phase reaction, and then grinding; optionally, the sintering temperature is 1650 to 1750° C., and the sintering time is 2 to 3 hours.

4. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the particle size of the glassy calcium silicate particles is 20-40 μm.

5. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the nano-silicon dioxide is added when the liquid phase system changes from light yellow to colorless and transparent during continuous stirring.

6. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the mass ratio of graphene oxide, glassy calcium silicate and nano-silicon dioxide is 1:1-3:10-25; optionally, the particle size of the nano-silicon dioxide is 20-50 nm.

7. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the solid-liquid ratio of the graphene oxide, glassy calcium silicate, nano-silicon dioxide and isopropanol is 1 g: 5-10 ml.

8. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (1), the solid-liquid ratio of the solid product to the saturated sodium hydroxide and / or potassium hydroxide solution is 1 g: 5-15 ml.

9. The method for preparing the cement mineral-water glass composite grouting material according to claim 1, characterized in that: In step (2), the heating temperature is 40-60° C. and the insulation time is 1-3 hours; optionally, slow stirring is performed at a rate of 30-50 r / min during the insulation process.

10. The method for preparing the cement mineral-water glass composite grouting material according to any one of claims 1 to 9, characterized in that: In step (3), the mass ratio of the sodium silicate and / or potassium silicate-graphene oxide-glassy calcium silicate, tricalcium silicate, dicalcium silicate and water is 1:0.5~0.8:0.2~0.5:0.3~0.5.

Citation Information

Patent Citations

  • Grouting material based on industrial-grade graphene oxide and preparation method thereof

    CN113149540A

  • Graphene oxide clay cement grouting material and preparation method thereof

    CN115745558A

  • Three liquid-typy grouting material and grouting method using the same

    KR101462448B1

  • Method and Materials to Convert a Drilling Mud into a Solid Gel Based Lost Circulation Material

    US20200407620A1

  • Concrete product and methods of preparing the same

    US20220024071A1